The Impact of Different Government Subsidy Methods on Low-Carbon Emission Reduction Strategies in Dual-Channel Supply Chain. (12th January 2021) - Che, Cheng; Chen, Yi; Zhang, Xiaoguang; Zhang, Zhihong
Abstract : With the implementation of national carbon emission reduction policies and the development of online shopping, manufacturers are making low-carbon efforts and selling products through dual channels. This paper constructs a dual-channel supply chain decision-making model composed of low-carbon emission reduction manufacturers and retailers and studies the optimal decision-making problem of the supply chain under subsidies by the government based on emission reduction R&D and per unit product emission reduction. The research results show the following: (1) when the government subsidizes emission reduction R&D, the emission reduction will have an impact on retailers' optimal prices, manufacturers' optimal wholesale prices, and optimal direct sales channel sales prices. The profit of the manufacturer increases with the increase in carbon emissions, and the profit of the manufacturer increases to a certain level and then appears to decline. (2) When the government adopts a subsidy method based on the emission reduction per unit product, the manufacturer's wholesale price and the selling price of direct sales channels, as well as the retailer's own optimal price, will increase with the increase in emission reductions. Retailers' profits will increase linearly with the increase in carbon emissions. Manufacturers' profits will first increase in a straight line and then increase in a curve.